1999
DOI: 10.1038/sj.bmt.1701556
|View full text |Cite
|
Sign up to set email alerts
|

High-dose therapy with autologous or allogeneic transplantation as salvage therapy for small cleaved cell lymphoma of follicular center cell origin

Abstract: Summary:Between 1985 and 1996, 51 patients with relapsed or refractory small cleaved cell lymphoma (SCCL) received high-dose chemotherapy ؎ TBI in conjunction with autologous (ABMT) (36 patients) or allogeneic transplantation (15 patients). Patients were eligible for ABMT if the bone marrow biopsy done prior to the planned transplant did not reveal microscopic involvement with SCCL. Patients receiving ABMT had a median age of 48 years, had received a median of 2.5 chemotherapy regimens prior to transplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…OS rates in these studies range between 55 and 81%. [7][8][9][10][11][12][13] A randomized phase III trial sponsored by the EBMTR that was closed prematurely reported a significant prolongation of both progression-free and OS with purged or unpurged ASCT compared to chemotherapy alone in this group of patients. 14 The progression-free survival at 2 years for patients receiving purged ASCT, unpurged ASCT, and chemotherapy was 55, 58, and 26%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…OS rates in these studies range between 55 and 81%. [7][8][9][10][11][12][13] A randomized phase III trial sponsored by the EBMTR that was closed prematurely reported a significant prolongation of both progression-free and OS with purged or unpurged ASCT compared to chemotherapy alone in this group of patients. 14 The progression-free survival at 2 years for patients receiving purged ASCT, unpurged ASCT, and chemotherapy was 55, 58, and 26%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the transplantation protocols and supportive care are reported elsewhere. 15,16 Evaluation and definitions…”
Section: Transplantation Protocolmentioning
confidence: 99%
“…Allogeneic blood stem cells were mobilized from healthy donors with recombinant granulocyte colony-stimulating factor (G-CSF; Amgen, Thousand Oaks, CA, USA), collected by apheresis and cryopreserved (one patient received non-cryopreserved blood alloSCT). 15,16 Day 0 for the recipient was the day of stem cell infusion. Eighteen recipients of related donor grafts received G-CSF post SCT until neutrophil recovery.…”
Section: Transplantation Protocolmentioning
confidence: 99%
“…It may be necessary to screen for the donor's t(14;18) status before using t(14;18) for monitoring minimal residual disease by RQ-PCR to exclude the possibility of confounding donor's t (14;18) [4][5][6][7][8][9][10][11] Allogeneic stem cell transplantation (allo-SCT) is of increasing interest as a therapeutic option for patients due to the potential of a graft-versus-lymphoma effect to provide long-term disease control. [12][13][14][15] We have recently reported that monitoring the tumor load of t(14;18) cells by real-time quantitative PCR (RQ-PCR) may predict the outcome of FL patients after allo-SCT. 16 Patients with tumor loads of greater than one t(14;18) cell per 10K total cells post transplantation have a higher risk of clinical relapse than those without.…”
Section: Discussionmentioning
confidence: 99%